2013
DOI: 10.1177/1759720x13483894
|View full text |Cite
|
Sign up to set email alerts
|

Milnacipran combined with pregabalin in fibromyalgia: a randomized, open-label study evaluating the safety and efficacy of adding milnacipran in patients with incomplete response to pregabalin

Abstract: Objective: To evaluate the safety, tolerability, and efficacy of adding milnacipran to pregabalin in patients with fibromyalgia who have experienced an incomplete response to pregabalin. Methods: In this randomized, multicenter, open-label study, patients received pregabalin 300 or 450 mg/day during a 4-to 12-week run-in period. Patients with weekly recall visual analog scale (VAS) pain score of at least 40 and up to 90, Patient Global Impression of Severity score of at least 4, and Patient Global Impression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Nearly all studies selected statistical methods (last observation carried forward) that bias results towards exaggerating the efficacy of drugs (Moore 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all studies selected statistical methods (last observation carried forward) that bias results towards exaggerating the efficacy of drugs (Moore 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Last observation carried forward can lead to overestimation of efficacy, particularly in situations where adverse event withdrawal rates differ between active and control groups. At this time it is unclear what strategy can actually be used to deal with missing data inside studies (Moore 2012). We examined and reported imputation strategies clearly.…”
Section: Methodsmentioning
confidence: 99%
“…A total of seven combination studies involving pregabalin were identified (summarized in Table 1; see also Table 3 of the Supplemental Online Material for more details of each individual study) [69][70][71][72][73][74][75]. The placebo-controlled clinical study in which pregabalin was added on top of an antidepressant [51] because has been discussed in detail above as the antidepressant was being administered for the treatment of depression alone and not FM.…”
Section: Combination Studiesmentioning
confidence: 99%
“…Based on withdrawals due to AEs, the tolerability of pregabalin in combination with another treatment was no worse when compared with placebo or either treatment when administered alone. It is worth noting that the majority of studies discussed here were conducted in relatively small patient populations, with some exceptions [71,73]. Nonetheless, these studies provide a platform for future large-scale, randomized, placebo-or comparator-controlled, double-blind trials of pregabalin in combination with other treatments.…”
Section: Combination Studiesmentioning
confidence: 99%
“…3,24 The effect sizes for nonpharmacological approaches tend to be larger than those for drugs, but combinations of drugs have only recently started to be tested. There have been some positive results, [25][26][27] emphasising the potential utility of a multimodal approach.…”
Section: Pathophysiologymentioning
confidence: 99%